Biochemical markers and emerging therapies for intestinal manifestation of graft-versus-host disease - Wiejak, Katarzyna; Przybyłkowski, Adam; Tomaszewska, Agnieszka (Frontiers in Immunology, 2025)
Graft-versus-host disease (GVHD) remains a potentially fatal complication of allogeneic hematopoietic stem cell transplantation (alloHCT). Gastrointestinal involvement, whether in acute or chronic GVHD, is associated with a poorer prognosis and poses significant diagnostic and therapeutic challenges. Numerous studies have attempted to identify markers that could facilitate the diagnosis and predict the course of GVHD. Among them, REG3α and ST2 currently show the greatest promise; however, comprehensive validation remains lacking. Although several new drugs have been approved for GVHD treatment in recent years and some modifications to GVHD prophylaxis have been adopted into clinical practice, further research are needed to validate biomarkers and explore new therapeutic targets, particularly in gastrointestinal GVHD. The review aims to summarize current research on GVHD biomarkers and emerging treatment targets, with a particular focus on gastrointestinal tract disease.